Effects of two teaching approaches on the explaining skill of medical clerks - De Leoz-Panigbatan, Amy M.
Physicians are inevitably called to be educators in varied circumstances. However, the Philippine Medical Curricula in general, offer no specific course that addresses the enhancement of the teaching skills of the aspiring doctors. The Pamantasan ng Lungsod ng Maynila College of Medicine (PLM-CM) was conceived to be a strong arm of the government of the city of Manila in catering to the medical needs of its underserved communities. Through its medical students who deliver patient and care-provider education in the community setting, the citizens of Manila are being armed with valuable information on the prevention of common diseases. At the Clerkship level which corresponds to the 4th year of Medical schooling, the students are assumed to be content experts relative to the community learners. With this expertise, comes the expectation that they are equipped with the ability to effectively communicate these necessary information that will help promote the citizen?s wellness. However, without a specific course that formally addresses the enhancement of the medical students? explaining skills, their ability to translate their knowledge into forms that are readily understood by their learners is at best, hoped for. This study looked into the effect of the introduction of microteaching, an innovative method of instruction that builds on feedback and on the opportunity to view oneself in a TV monitor, on the explaining skill of the medical clerks. The effect of microteaching was compared to that of the traditional method of learning how to teach. Fifty-three 4th year medical students from the Pamantasan ng Lungsod ng Maynila were asked to render 5-10 minute explanations on a topic of their choice in front of their peers while being video-recorded. Using the Skill Observation Record on Explaining (based on the Sydney Micro Skills Redeveloped) as a tool, the explaining skills of these medical clerks were rated by themselves, and their peers. Half of the group underwent microteaching and the other half, the traditional method of learning how to teach. The medical clerks were then asked to render another 5-10 minute explanation on the same or on a different topic which were again video-recorded, and rated by self and their peers using the same tool. The video-recorded materials were shown to experts who were kept blind as to the timing of the video clips and the method of instruction introduced to each medical student. T-test analysis of the pre- and post-test scores of the microteaching group pointed to a statistically significant difference at alpha=.01. Comparison of the difference in the pre- and post-test ratings of the Microteaching and Traditional method of learning group using ANOVA repeated measures, showed significant difference (alpha = 0.05) in the mean scores, implying greater improvement in the explaining skills of those who underwent microteaching compared to the traditional method, as rated by peers and by the experts. Microteaching proved to be a useful method in improving the explaining skill of medical clerks. Its usefulness surpassed that of the Traditional method of learning how to teach. Introduction of a course in Microteaching is a strategy proven to improve the skills of explaining among the 4th year medical students, who despite the content expertise gained during the first three years of medical schooling have the pressing need to advance in the delivery of the valuable information to their target learners. These findings offer before us a strategy that will help our professionals fulfill their obligation of being mentors to their fellow health practitioners, to the other health workers, care providers and to their patients. It is recommended that a Microteaching class on the Explaining Skill be integrated into the existing medical curriculum of the Pamantasan ng Lungsod ng Maynila, College of Medicine, as well as those of the other academic medical curricula in our country.